2020
DOI: 10.1186/s12871-020-0934-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malignant hyperthermia diagnosis in obstetric patients in the United States, 2003 to 2014

Abstract: Background: The cost-benefit of stocking dantrolene in maternity units for treating malignant hyperthermia (MH) has been recently questioned because of the low incidence of MH crisis in the general population and the low utilization of general anesthesia in obstetrics. However, no study has examined the prevalence of MH susceptibility in obstetrics. This study aimed to assess the prevalence of MH diagnosis and associated factors in obstetric patients. Methods: Data for this study came from the National Inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The fact is far away from the recommendation of the MHAUS that dantrolene should be immediately available (for administration within 10min) in operating room areas. 27 , 28 Indeed, as the only disease-specific drug available for MH, lack of IV dantrolene in most Chinese hospitals is the major problem in MH treatment. 14 , 29 Only few hospitals in China stored IV dantrolene because of the high cost and low utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The fact is far away from the recommendation of the MHAUS that dantrolene should be immediately available (for administration within 10min) in operating room areas. 27 , 28 Indeed, as the only disease-specific drug available for MH, lack of IV dantrolene in most Chinese hospitals is the major problem in MH treatment. 14 , 29 Only few hospitals in China stored IV dantrolene because of the high cost and low utilization.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 The results from the last decade of research are similar to previous studies, with a prevalence of MH diagnosis arranging from 0.18 per 100 000 to 3.9 per 100 000. [20][21][22][23][24] As a rare disease, the overall reported incidence of MH varied widely in different studies because of many factors. Studies have shown that general anesthesia was more likely to cause MH than other types of anesthesia.…”
Section: Morbiditymentioning
confidence: 99%
“…24 Obstetric patients, especially during vaginal delivery, usually had a lower incidence of MH, at 0.29 per 100 000. 23…”
Section: Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Presentation within the child population is similar to adults, with muscle rigidity, hypermetabolism and arrhythmias, and neonatal presentation is likely to fall under the same umbrella. Estimated incidence in the general surgical population is between 1:3000 to 1:100 000 and 1:125 000 in the US obstetric population 2 3…”
Section: Introductionmentioning
confidence: 99%